KEMANJURAN TEKNIK SELF-MANAGEMENT DALAM BINGKAI BIMBINGAN KELOMPOK UNTUK MENCEGAH PERILAKU PROKRASTINASI AKADEMIK SISWA SMP - Ramadhani Sutarno, Shafira; Afrilianto, M; Utomo, Prio (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Academic procrastination is a negative thing that must be avoided, especially by students. The objective of this study is to assess the effectiveness of group guidance services that employ self-management ways to reduce academic procrastination in junior high school students. This study employs mixed methods, using an explanatory sequential research design. The subjects in this research were 8 experimental group students and 8 control group students who had high academic procrastination. The results of the research show that the comparison between the pretest and posttest questionnaires shows that there is a decrease in academic procrastination. These results can be proven in the independent sample test, that the sig (2-tailed) value is 0.000 < 0.05, This indicates that Ho is rejected but Ha is accepted. Thus, group guiding services paired with self-management abilities might help reduce academic procrastination.